PRIMARY EXPERIENCE OF NON-REFLECTIVE SUBJECTIVE CONSCIOUSNESS AS A TOPOS OF RELATIONSHIP / FORMAL SIMILARITY OF INDO-EUROPEAN LANGUAGES (on the material of focal unities of words-photophenomena) - Shevkun , Eleonora (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article is devoted to the theoretical and philosophical foundations of the research, which are based on the model of cognition, formed in the womb of the post-non-classical philosophical paradigm as a synthesis of phenomenology and existentialism. Rejection of classical epistemology (knowledge of being through essence) leads to the focus of research on the sphere of human subjectivity. Consciousness, intentionality, and experiences embedded in the meanings of existence are revealed by describing the topological space of phenomenological consciousness through modeling the complete act of phenomenization; in the language plane, a complete analysis of the phenomena of light nature is the focus of the emergence of words-photophenomena. the mentioned conceptual frameworks serve as the theoretical basis for comparing and comparing closely related languages of the Indo-European language family in combination with the empirical work of historical comparativism / comparative historical method; etymological analysis of linguistic material and the identification of chains-linkages of roots-photoetymons in Indo-European languages.The author's personal contribution consists in the APPLICATION OF ACCURATE AND VALID principles of the complex philosophy of language – the synthesis of phenomenology and existentialism, which open a new perspective in the centuries-old search for a solution to the problem of kinship / formal similarity of Indo-European languages.The departure from methodocentrism and the application of theoretically multiple models of the conceptualization of subject language opens up new opportunities for alternative modeling of the probabilities of appearance – the description of existential words of the light nature as complicit in the focus of the internal – a complete act of phenomenization in the modality of possibility / probability. Anthropological investigations as a manifestation of the internal deep beginnings of the subject of existence allowed us to put forward a hypothesis about the relative nature of the pragmatic component in the acts of the primary non-reflective experience of discovering being in the world and the probabilistic bringing to the fore of the a priori given of Freedom under the condition of a phenomenal relationship to the world. Empirical material of the study – focal units of words of photophenomena, which speak about the world and human existence in it, include a significant amount of language material from closely related language groups of the Indo-European family.__________References:• Selivanova, O. O. Suchasna lingvistyka: terminologichna encyklopedija (Poltava: Dovkillja–K, 2006): 718.• Mariten, Zhak. Jevropejs'kyj slovnyk filosofij: Leksykon neperekladnostej, per. z franc. pid ker. Barbary Kassen, https://issuu.com/duh-i-litera/docs/vep_i_extract• Voznjuk, A. V. Pro sub'jektyvnyj dosvid u piznanni svitu (Zhitomir: Koob publications, 2022), chrome-extension://efaidnbmnnnibpcajpcglclefindmkaj/http://eprints.zu.edu.ua/ 336551/Voznjuk_O%20sub#ektivnom%20opyte%20MONO%202022.pdf• https://coollib.com/b/162143/read• https://booksonline.com.ua/view.php?book=104956• https://booksonline.com.ua/view.php?book=135864• https://www.phantastike.com/other/slovar_terminov/ djvu/view/
Keywords: photophenomenon, the word-photophenomenon, phenomenological consciousness, primary experience of non-reflective consciousness, first event-existential intentional-semantic constants, complete act of phenomenization, sociogenesis consciousness